DETERMINANTS OF WOMEN EMPOWERMENT IN RURAL PUNJAB, PAKISTAN - Zeba Andleeb; Izhar Ahmad Khan; Naveed Farah; Babar Shahbaz (International Journal of Contemporary Issues in Social Sciences, 2024)
This study was designed to explore the socio-cultural impediments of women empowerment in rural Punjab Pakistan. Women empowerment has emerged as a crucial agenda in the World, aiming to promote gender equality and provide women with equal opportunities to participate and thrive in various spheres of life. However, the realization of women empowerment faces numerous socio-cultural impediments that hinder progress towards this goal. Deep-rooted patriarchal norms and gender stereotypes perpetuate the subordinate status of women, limiting their access to education, employment, and decision-making roles. Cultural traditions and practices, often steeped in patriarchal ideologies, pose significant challenges to women’s empowerment. These practices include early and forced marriages, female genital mutilation, and restrictions on mobility and social interactions. Such traditions not only curtail women’s individual rights but also perpetuate gender inequalities across generations. Discriminatory social norms and attitudes marginalize women in various domains, including politics, economics, and public spaces. These norms reinforce a biased perception of women’s abilities, devaluing their contributions and impeding their participation in decision-making processes. The overall objective of study was to explore the current socio-cultural impediments of women empowerment in rural areas of Punjab, Pakistan. A sample size of 600 respondents was taken at random to collect quantitative data from the three districts of Punjab Multan, Faisalabad and Sargodha. Quantitative data were analyzed using SPSS and presented descriptively and conclusively. The results show that there is a strong connection between socio-cultural barriers and women’s empowerment in the study area. Most respondents reported that the lack of women’s active participation in decision-making in rural areas of Punjab has significant effects on empowerment. As the majority of respondent testified the low economic opportunities to females, we now had to see that between religion and culture which factor is placing more hurdles on the way of economic empowerment in tribal areas. The quantitative findings also suggest that the majority of respondents believed that poverty is, at least to some extent, the cause of women’s underdevelopment. Large numbers of respondents see customs as an obstacle to women’s empowerment. Moreover, legislative reforms and strict enforcement are necessary to protect women’s rights and eliminate discriminatory practices.